CORAK HARAKI DALAM PENAFSIRAN SAYYID QUTB - qardlawi, muhammad yusuf (Fakultas Ushuluddin, Adab, dan Dakwah UIN Sultan Aji Muhammad Idris Samarinda, 2023)
This research wants to present the features found in the interpretation of Fi Ẓilalil Qur'an by Sayyid Qutb. By conducting a study of certain verses interpreted by Sayyid Qutb, tendencies in his interpretation can be identified. In this research it can be concluded that the interpretation of the Fi Ẓilalil Qur'an has a haraki style. Tafsir with a haraki style is an interpretation that links the verses of the Koran to the conditions of social movements that occur at that time or in the future. Interpretation with this style is certainly a new style in interpretation. With this style, it is hoped that researchers will have diversity in research related to the interpretation of the Al-Qur'an.